The bases of clearing of the owner of source of the raised danger from the duty of harm compensation - Alieva, L.R. (KSU publ, 2011)
Article is devoted to the bases of release of the owner of a source of the increased danger from a duty of compensation of harm. The main problems of compensation of the harm caused by a source of increased danger are considered. The author analyzes the existing civil legislation, brings up a question of value of fault of the causing which have injured in cases to it harm the owner of a source of the increased danger. The subjective bases of liberation of the owner of a source of the increased danger from compensation of harm are investigated. Are exposed to the analysis also various dock-trinalnye of provision on the main issues concerning delicate obligations.
Keywords: the Civil legislation; compensations of the harm; compensation of harm; caused spring the heightened danger; release of owner spring heightened danger from compensation harm; the delictual obligation